Social policy diffusion in South Asia. Issue 1 (2nd January 2017) - Betz, Joachim; Neff, Daniel
ABSTRACT: South Asia has seen the almost simultaneous introduction of contribution-free social schemes in employment, health, education and pensions which are often strengthened by constitutional amendments and the right to information about government acts and procedures for normal citizens. Given the diverging economic, political and social composition of the countries of the region the near simultaneous introduction of the rights-based cash transfer programmes might be attributed to regional policy diffusion, caused either by some common pressures, learning from neighbours, or emulation. Using the case of employment guarantee programmes we contribute to the diffusion literature by showing that the schemes were not copied fully, but adapted to the national social, political and financial circumstances of the countries, built on the respective programme predecessors or not copied at all. Governments in the region were able to choose not only the timing of introduction but also the scope, coverage and generosity as well as their regulatory framework for programme execution and monitoring. We argue that programme adoption is more likely if the programmes in question are compatible with the ideological leanings of the government, fit with the international social practice and compatible with already existing schemes. However, some similarities between the employment programmes in South Asia could be the result of the influence of external development actors with the result that former rather different programmes become alike.